Using Revised Bloom’s Taxonomy to Evaluate Higher Order Thinking Skills (Hots) in Reading Comprehension Questions of English Textbook for Year X of High School - Atiullah, Kurnia; Wuli Fitriati, Sri; Rukmini, Dwi (Universitas Negeri Semarang, 2019)
Higher Order Thinking Skills (HOTS) has been widely recognized as a set of important devices of cognitive development. The research was conducted to evaluate the availability of higher order thinking skills in reading comprehension questions of the English textbook for Year X of high school published by ministry of education. There are 158 reading comprehension questions from 15 reading texts which are analyzed using revised Bloom’s taxonomy. An intuitive approach to the analysis of qualitative data is taken for the study in which an individual researcher intuitively relates data from various instruments to each other (Smaling, 1987) in Meijer, et al (2002, p. 146). The data were analyzed qualitatively to determine the cognitive level of each questions according to revised Bloom’s taxonomy, Question types based on which cognitive process is required to answer and forms of questions. The result shows that majority of reading comprehension questions in the textbook being studied is in the lowest level of revised Bloom’s taxonomy; remembering with 134 items whereas higher order thinking skills are only found in 24 out of 158 items. It was concluded that the reading comprehension questions of the English textbook for Year X of high school is lack of higher order thinking skills. The result of the study is expected to benefit the English teachers, textbook writers and further researchers to elaborate the implementation of higher order thinking skills in English teaching and learning.